2010
DOI: 10.1111/j.1349-7006.2010.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved anti‐tumor activity of stabilized anthracycline polymeric micelle formulation, NC‐6300

Abstract: Anthracyclines have long been considered to be among the most active agents clinically available for the treatment of breast cancer despite their toxicity. To improve their pharmacological profiles, a new macromolecular prodrug, denoted NC-6300, was synthesized. NC-6300 comprises epirubicin covalently bound to polyethyleneglycol polyaspartate block copolymer through an acid-labile hydrazone bond. The conjugate forms a micellar structure spontaneously in aqueous media with a diameter of 60-70 nm. The block copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 26 publications
2
74
0
1
Order By: Relevance
“…Of these, polymeric, micelle-based, anticancer drugs were originally developed by Kataoka et al [1][2][3] The assumed bases of higher effectiveness and lower toxicity of anticancer nanoDDSs are the "enhanced permeability and retention (EPR) effect". 4 In addition to the EPR effect, the drug release rate from macromolecular DDSs is also critical to efficacy, 5,6 for the following two reasons: (1) time course of plasma concentration of the naked drug is important, since it is the loaded drug that has toxic effects for both normal and tumor cells; (2) not all nanoDDSs reach their target tissue, releasing the loaded drugs in plasma. The release rate of loaded drugs with polymeric micelles can be optimized by various methods such as redesigning the chemical bond between polymer and drug; however, with liposomes, it is not easy to control release rate, because they have a stable lamella of lipid bilayer on the surface to contain drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, polymeric, micelle-based, anticancer drugs were originally developed by Kataoka et al [1][2][3] The assumed bases of higher effectiveness and lower toxicity of anticancer nanoDDSs are the "enhanced permeability and retention (EPR) effect". 4 In addition to the EPR effect, the drug release rate from macromolecular DDSs is also critical to efficacy, 5,6 for the following two reasons: (1) time course of plasma concentration of the naked drug is important, since it is the loaded drug that has toxic effects for both normal and tumor cells; (2) not all nanoDDSs reach their target tissue, releasing the loaded drugs in plasma. The release rate of loaded drugs with polymeric micelles can be optimized by various methods such as redesigning the chemical bond between polymer and drug; however, with liposomes, it is not easy to control release rate, because they have a stable lamella of lipid bilayer on the surface to contain drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugate spontaneously forms a micellar structure with a diameter of 40 -80 nm in aqueous media, as reported previously (53). In vitro findings indicated that it exhibited pH-dependent EPI release, namely, the release of EPI from NC-6300 accelerated under increasingly acidic conditions.…”
Section: Preparation and Characterization Of Nc-6004mentioning
confidence: 50%
“…Adaptive designs can provide robust answers to study questions and in the meantime reduce the total number of patients required, resulting in potentially reduced costs and shorter timelines than traditional trials. The session concluded with Iulian Bobe from NanoCarrier sharing his company's experience in clinical development program for nanomedicines (20).…”
Section: Session V: Clinical Studiesmentioning
confidence: 99%